Hubungan Pemberian Makanan Pendamping ASI (MP-ASI) Dengan Status Gizi Pada Balita Di Puskesmas Satelit Bandar Lampung. - Riska Wandini; Setiawati Setiawati; Dea Pratiwi (Malahayati Nursing Journal, 2021)
ABSTRACT : THE CORRELATION BETWEEN WEANING FOODS AS BREAST MILK COMPLEMENT AND NUTRITIONAL STATUS OF TODDLERS AT SATELIT HEALTH CENTER OF BANDAR LAMPUNG  Introduction : According to pre-survey data of Satelit Health Center on 16 February 2020, there were ten babies aged 6 to 18 months taking height and weight measurement and age record, revealing that six of them having low nutritional status with 2SD and the other two babies had over nutritional status with 2 SD. After interviewing the mothers, it was known that six women did not know what weaning food is even they did not know the menu or type of the weaning food to be given.  The objective of this study was to identify the correlation between weaning foods as breast milk complement and nutritional status of toddlers at Satelit Health Center of Bandar Lampung in 2020.Method : This was a quantitative study with survey analytical design and cross sectional approach. The population of this study consisted of 46 mothers registered at Satelit Health Center of Bandar Lampung. The sampling technique was total population resulting 46 respondents whose babies are 6 to 18 months. Results: It was known in Satelit Health Center of Bandar Lampung that there were 24 respondents (52.2%) who gave weaning foods properly to their babies.  Unfortunately, there were 27 respondents (58.7%) having babies with low nutritional status.Conclusions : There is correlation between weaning food as breast milk complement and nutritional status of toddlers aged 6 to 18 months at Satelit Health Center of Bandar Lampung in 2020 with p value 0.032 or p value 0.05. The heath practitioners at the health center should inform the mothers about menus of weaning foods for breast milk complement based on the need of the toddlers.  The facilities on weaning foods of the health center should be provided.Keywords      : weaning foods Nutritional Status   INTISARI : HUBUNGAN PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) DENGAN STATUS GIZI PADA BALITA DI PUSKESMAS SATELIT BANDAR LAMPUNG Pendahuluan : Berdasarkan data prasurvey Di Puskesmas Satelit Pada Tanggal 16 Februari 2020, diketahui ada 10 bayi usia 6-18 bulan, dimana setelah dilakukan pengukuran TB, BB dan pencatatan usia, diketahui 6 bayi mengalami gizi kurang dengan hasil pemeriksaan -2SD dan 2 bayi mengalami gizi lebih dengan hasil pemeriksaan 2SD. Setelah dilakukan wawancara kepada ibu dengan bayi, 6 ibu mengatakan bahwa tidak mengetahui tentang MP-ASI baik menu apa saja yang harus diberikan ataupun jenis MP-ASI yang diberikan. Tujuan penelitian ini adalah diketahui hubungan pemberian makanan pendamping ASI (MP-ASI) dengan status gizi Pada Bayi Di Puskesmas Satelit Bandar Lampung Tahun 2019Metode : Jenis penelitian kuantitatif rancangan penelitian menggunakan survei analitik dengan menggunakan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh ibu yang mempunyai Bayi Di Puskesmas Satelit Bandar Lampung berjumlah 46 responden dengan sampel dalam penelitian ini adalah seluruh ibu yang mempunyai bayi usia 6-18 bulan Di Puskesmas Satelit Bandar Lampung berjumlah 46 responden. Dalam penelitian ini teknik sampling yang digunakan adalah total sampling Hasil : Diketahui bahwa Di Puskesmas Satelit Bandar Lampung Tahun 2020, sebagian besar responden memberikan MP-ASI dengan baik yang berjumlah 24 responden (52,2%) dan responden yang mengalami gizi kurang baik yang berjumlah 27 responden (58,7%)Kesimpulan : Terdapat hubungan pemberian makanan pendamping ASI (MP-ASI) dengan status gizi pada bayi usia 6-18 bulan Di Puskesmas Satelit Bandar Lampung Tahun 2020 dengan p-value 0,032 atau p-value 0,05. Diharapkan kepada pihak Puskesmas agar dapat membuat daftar menu pemberian MP-ASI sesuai dengan kebutuhan balita dan menyediakan fasilitas sarana prasarana tentang menu MP-ASI sesuai dengan kebutuhan balita. Kata Kunci         : MP-ASI Status Gizi